PENERAPAN MODEL PROJECT BASED LEARNING (PjBL) UNTUK MENINGKATKAN KEMAMPUAN BERPIKIR KRITIS PESERTA DIDIK PADA MATERI KOROSI - VINA N VAN HARLING; Stefany Margareta Martono (SOSCIED, 2023)
The development of technology in education in addition to playing a role in delivering teaching can also have a great influence and impact on students. For this reason, in today's world of education, students are expected to be able to think critically. Critical thinking as a complex process requires a high level of cognitive processing of information. This learning concept can be applied to chemistry subjects such as to corrosion materials. The study used a mixed research method involving quantitative and qualitative methods. Sample selection using purposive sampling techniques based on consideration of learning outcomes, student learning styles based on considerations. The data obtained were analyzed using Miles and Huberman data analysis techniques, and Paerson correlation. The application of the project-based learning model (PjBL) on corrosion material has been well applied so as to improve the critical thinking ability of students. In addition, there is a correlation between the application of the project-based learning model (PjBL) to the critical thinking skills of learners against corrosion materials. The test results obtained a large correlation value between syntactic variables and students' critical thinking skills of 0.991, and significance of 0.087.